Aqueous mixtures of cornstarch and Pluronic® F127 studied by experimental and computational techniques - Baldassa, Monize A.B. [UNESP] (2022)
The possibility of interaction between cornstarch (CS) and amphiphilic molecules, such as the micelle-forming triblock copolymer Pluronic® F127 (F127), also known by Poloxamer 407, indicates that CS-F127 aqueous mixtures can regulate either the starch solubility or the copolymer micellization. Herein experimental and computational techniques were used to investigate CS-F127 aqueous mixtures aiming to highlight the role of these compounds on the molecular complexation. Dynamic light scattering results show that CS in water is highly polydisperse, while the F127 concentration and temperature influence the micellization process and the interaction with CS. Circular dichroism data of CS supernatants indicate the existence of small helical-like granules (Dh ≈ 800 nm) in the CS-F127 mixed aqueous solutions at 25 °C. UV–Vis spectrophotometry shows a small absorption band around 267 or 275 nm characteristic of micelles, granules, or molecular complexes, while FTIR and X-ray diffractometry indicate negligible structural changes. Lugol iodine tests at 25 °C show that both the precipitate and supernatant in the mixtures undergo some structural changes also indicating molecular complexation. Molecular dynamic simulations show the formation of stabilized inclusion complexes (V-amylose), where the propylene oxide segment of the copolymer inside the amylose helix and the ethylene oxide branches facing the aqueous media. These results together reveal weak CS-F127 interactions, evidencing a small solubility of CS both in the absence and presence of F127 as a solubilizing agent. Furthermore, moderate CS amounts do not change the F127 micelle structure.